Saturated abnormal NHC-gold(I) complexes: synthesis and catalytic activity - Manzano, Rubén; Rominger, Frank; Hashmi, A. Stephen K. (Organometallics, 2013)
New saturated abnormal N-heterocyclic carbene complexes of gold(I) have been prepared by a 1,3-dipolar cycloaddition of an in situ generated azomethine ylide with an isocyanogold(I) choride. A series of different substituents on the nitrogen atom of the 1,3-dipole are tolerated without problem. Substitutents on a carbon atom of the 1,3-dipole are problematic in the case of the isocyanogold(I) chlorides; only low yields are obtained. However, the corresponding isocyanogold(I) iodide shows good reactivity, and these abnormal N-heterocyclic carbenes bear the substituent in a position α to the carbene carbon, as proven by a crystal structure analysis of one of the products. Some of the new saturated abnormal N-heterocyclic carbene complexes were then tested in the gold-catalyzed phenol synthesis; moderate turnover numbers of 252-380 could be reached.